Peran Strategis Fatwa MUI dan Pengkaderan Ulama Perempuan untuk Kemaslahatan Umat dan Perlindungan Perempuan - Muthmainnah, Yulianti - (IJouGS: Indonesian Journal of Gender Studies, 2024)
AbstrackThe Indonesian Ulema Council (MUI) has three strategic roles: khodimul ummah, himayatul ummah, and shodiqul hukumah. Carrying out these three roles, MUI formulates religious fatwas that are also related to women's issues. Such as fatwa on halal ingredients for cosmetics and dress code, sexuality (abortion, female circumcision), and marriage (children and family relations). The two questions of this paper are whether women's life experiences are taken into consideration in the formulation and decision of fatwas? Why does MUI fatwa in fact get rejection from women's groups? To answer them, this paper uses a qualitative study, describing and analyzing MUI fatwas for the period 2010-2020 and several selected fatwas outside those years that are in accordance with the theme. This paper departs from the assumption that Indonesian society (including women's groups) actually needs MUI fatwas. This paper contributes to provide information on the strategic role of MUI for the protection of women through its fatwas and at the same time MUI still needs public input, especially women scholars, so that the fatwas produced are in favor, protecting women. And the importance of MUI making women as the subject of fatwa and not the object of fatwa, getting closer to women's experience; hearing and asking women's opinions or considering fatwas from women scholars, so that the fatwa produced by MUI suits women's needs and does not cause rejection. Key words: MUI fatwas, women ulama, women experiences AbstrakMajelis Ulama Indonesia (MUI) memiliki tiga peran strategis yakni khodimul ummah, himayatul ummah, dan shodiqul hukumah. Menjalankan ketiga peran tersebut, MUI merumuskan fatwa keagamaan yang juga terkait isu perempuan. Seperti fatwa bahan halal untuk kosmetika dan tata cara berpakaian, seksualitas (aborsi, sunat perempuan), dan perkawinan (anak dan hubungan keluarga). Dua pertanyaan tulisan ini adalah apakah pengalaman hidup perempuan menjadi pertimbangan dalam perumusan dan keputusan fatwa? Mengapa fatwa MUI kenyataannya mendapatkan penolakan dari kelompok perempuan? Untuk menjawabnya, tulisan ini menggunakan kajian kualitatif, mendeskripsikan sekaligus menganalisis fatwa MUI periode tahun 2010-2020 dan beberapa fatwa terpilih di luar tahun tersebut yang sesuai tema. Tulisan ini berangkat dari asumsi bahwa masyarakat Indonesia (termasuk kelompok perempuan) sejatinya membutuhkan fatwa MUI. Tulisan ini berkontribusi memberikan informasi peran strategis MUI untuk perlindungan perempuan melalui fatwa-fatwanya dan pada saat yang sama MUI tetap membutuhkan masukan masyarakat, terutama ulama perempuan, agar fatwa yang dihasilkan berpihak, melindungi perempuan. Dan pentingnya MUI menjadikan perempuan sebagai subyek fatwa dan bukan objek fatwa, mendekatkan diri pada pengalaman perempuan; mendengar dan meminta pendapat perempuan atau mempertimbangkan fatwa-fatwa dari ulama perempuan, agar fatwa yang dihasilkan MUI sesuai kebutuhan perempuan dan tidak menimbulkan penolakan Kata kunci: fatwa MUI, ulama perempuan, pengalaman perempuan